The Significance of Toshihiko Izutsu’s Legacy for Comparative Religion - Nakamura, Kojiro (2009)
Toshihiko Izutsu explored the Oriental philosophies and clarified their comprehensive structural framework by using comparative philosophy and linguistic philosophy. Izutsu made three contributions that are deemed especially crucial to the study of comparative religion. First, the attitude of empathy he proposed and applied to himself, and his strict methodology of semantics in interpreting philosophical texts. This attitude is also important when one is trying to understand the faith of others. Second, his delineation of the scheme of the basic structure of Oriental philosophy for the comparative study of religions. Third, his study of Oriental (mystical) philosophy is a significant contribution to the study of mysticism. However, there are still problems which remain to be addressed in comparative religion.